Making great illustration - Brazell, Derek; Davies, Jo (London A&C Black Publishers, 2011)
This text looks at some of the world's best illustrators, providing an insight into the creation of illustration from concept to finished work, and offering information on individuals not available elsewhere. The book covers a wide range of illustrative practice.
Introduction / Derek Brazell and Jo Davies -- Foreword -- Design and advertising -- Fiction -- Decorative illustration and merchandising -- Editorial and political illustration -- Typographical -- Children's publishing -- Graphic literature -- Fashion illustration -- Topographical illustration -- Authorial practice -- The photography -- Index -- The authors.
First published in Great Britain in 2011.
Keywords: Graphic arts -- Technique; Illustrators; Graphic artists